Quasi-10-day wave and semi-diurnal tide nonlinear interactions during the southern hemispheric SSW 2019 observed in the northern hemispheric mesosphere - He, Maosheng
Sudden stratospheric warming events occur typically over the winter Arctic and are well-known for being accompanied by diverse waves. A rare SSW occurred in the southern hemisphere in September 2019. Here, we combine mesospheric observations from the northern hemisphere to study the wave activities before and during the warming event. A dual-station approach is implemented on high-frequency-resolved spectral peaks to diagnose the horizontal scales of the dominant waves. Diagnosed are multiple tidal components, multiple Rossby normal modes, and two secondary waves arising from nonlinear interactions between a tide and a Rossby wave. Most of these waves do not occur in a climatological sense and occur around the warming onset. Furthermore, the evolution of these waves can be explained using theoretical energy arguments.